Geography and religion: Trends and prospects - Kong, Lily (Institutional Knowledge at Singapore Management University, 1990)
That geography and religion can and do meet to form a valuable focus of inquiry has not always been immediately apparent. While the study of religions has engaged the attention of a large and ever-widening circle of scholars, research has tended to proceed under the varied rubrics of sociology, anthropology, philosophy, history, and certainly, theology. Classics that have had significant impact on the development of 'religious thought' have emerged from the pens of scholars professing several diverse disciplines. For instance, Weber (1904-1905), Durkheim (1976), Otto (1950), and Eliade (1959) represent but a sample of the multifarious writings that have shaped much of the thinking of students of religion. These diverse sources amply illustrate, inter alia, the potential for multidisciplinary work. Given such diversity of interests and perspectives, what contributions have geographers made in the field of religion? This paper reviews geographical research in this direction, focusing primarily on efforts in the Anglophone world. The bulk of it covers the main themes in religiogeographical research, but it is not exhaustive; nor is it purely an annotated bibliography. Rather, it is the aim here to tease out from the apparent diffusion of themes, the main preoccupations of geographers thus far, and to evaluate the significance of these works to date.